Effect of the secretory small GTPases Rab27B on breast cancer growth, invasion, and metastasis - Hendrix, A. (2010)
Methods Expression of green fluorescent protein (GFP) fused with wild-type Rab3D, Rab27A, or Rab27B, or Rab27B point mutants defective in GTP/GDP binding or geranylgeranylation, or transient silencing RNA to the same proteins was used to study Rab27B in estrogen receptor (ER)-positive human breast cancer cell lines (MCF-7, T47D, and ZR75.1). Cell cycle progression was evaluated by flow cytometry, western blotting, and measurement of cell proliferation rates, and invasion was assessed using Matrigel and native type I collagen substrates. Orthotopic tumor growth, local invasion, and metastasis were analyzed in mouse xenograft models. Mass spectrometry identified proinvasive growth regulators that were secreted in the presence of Rab27B. Rab27B protein levels were evaluated by immunohistochemistry in 59 clinical breast cancer specimens, and Rab3D, Rab27A, and Rab27B mRNA levels were analyzed by quantitative real-time polymerase chain reaction in 20 specimens. Statistical tests were two-sided.